Implementasi Program Mini Market Day Dalam Menumbuhkan Rasa Percaya Diri Anak Usia 5-6 Tahun - Rahmania, Siti; Durrotun Nasikhah, Ikha (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The purpose of this study is to describe the implementation of the mini market day program in fostering self-confidence in children aged 5-6 years through hands-on learning experiences. This study adopted a descriptive qualitative framework, with direct observations conducted with 17 students in group B. The data collection technique used in the study was observation, and data reduction techniques were used for analysis. The results indicate that the mini market day program plays a role in fostering children's self-confidence, as evidenced by their ability to speak confidently in public, interact with peers, and make independent decisions. This activity also trains children to express opinions, manage emotions, and consistently complete roles. Thus, mini market day is a contextual learning strategy that contributes to the socio-emotional development of early childhood.